Produção biotecnológica de xilitol a partir da fração hemicelulósica da fibra de sisal - Xavier, Franklin Damião (2016)
Sisal is a typical plant of the northeast, being resistant to dry climates. Brazil is the largest producer and exporter of the fiber, with 50% of world production. Sisal is a potential feedstock for the production of xylitol due to its lignocellulosic composition containing high sugar content. This study aimed to evaluate the potential of the hemicellulose fraction of sisal fiber for production of xylitol, in addition to determining the lignocellulosic composition, the most appropriate pretreatment to remove xylose and optimum conditions for fermentation. The pretreatments were carried out in stainless steel reactor for 1 hour 1:10 (w/v) sisal fiber/acidic or basic solution. The sisal fibers showed better lignocellulosic composition for xylitol production other biomasses currently used, for example, bagasse from sugar cane, corn stover, due to exhibit a greater amount of hemicellulose, about 10% more, and lower lignin content. The pretreatment acid, dilute sulfuric acid, xylose removal was more effective under conditions of higher acid content (2,5%) and temperature (120 ºC). In alkaline pretreatment it was observed that there was no removal of the hemicellulose fraction, since the treatment basic/acid solubilization xylose was inferior to the single acid treatment. The effectiveness of the pretreatment acid was confirmed by ray-x diffraction, scanning electron microscopy, Thermogravimetric and Infrared. In the XRD patterns was observed an increase in the crystallinity of the treated sample due to the removal of amorphous components (hemicellulose) in TG curves second mass loss phase characterized depolymerization of hemicellulose with a reduction of 20% of the material between fiber in nature and treated. In the micrographs that found after pretreatment with acid the outer layer of the fibers was removed, and cleaving the more complex structure existed before making visible the cellulosic fibrillar structure. In the best condition was observed hydrolyzate liquor produced in large scale and this was fermented using yeast Candida guilliermondii CCT 1516. At 96 hours there was the maximum production of xylitol, 3,14 g/L, but liquor from the fiber sisal showed levels of acetic acid (5,86 g/L) above those permitted. The conversion factor xylose to xylitol, which when production was maximum, was 0,32 g/g xylose and xylitol in conversion efficiency was 35%. In the fermentation process it was observed that the acetic acid has interacted with the microorganism so as to reduce xylose to xylitol conversion. Therefore, the sisal fiber showed satisfactory performance even in conditions where fermentation would be disadvantaged, producing xylitol.